Karakterisasi Sensor LDR dan Aplikasinya pada Alat Ukur Tingkat Kekeruhan Air Berbasis Arduino UNO - Bowo Eko Cahyono; Ina Dwi Utami; Novia Puji Lestari; Nur Shabrina Oktaviany (Department of Physics, Faculty of Mathematics and Natural Sciences, University of Lampung, 2019)
A system of monitoring turbidity levels in real time using an LDR sensor has been designed and implemented. This study aims to characterize the LDR sensor and subsequently the results are used as a basis in the application of the deterioration system design for water turbidity levels. The characterization results show that the LDR sensor has a linearity of 90.86% and sensitivity of 0.0082 mV per lux. After being applied in measuring instruments the light intensity of the sensor has a precision level of 92.58% and the level of accuracy of the measurement results is an average of 87.89%. Based on the results of the design that has been carried out this instrument is able to turn on the water pump for the purification process automatically when the intensity of back scattering is less than 72 lux